Letter from Roger Casement to Francis H. Cowper, saying he is bidding the Foreign Office "adieu for a time" before checking into hospital for Christmas, - Casement, Roger, 1864-1916 (1904)
Casement encloses some money for lottery tickets and a letter for "O'Neill" [not extant] for Cowper to pass on.